Supportive Care for People With Disabilities as Working Partnerships With Their Assistance Dogs Are Ending: A Perspective From Veterinary Oncology - Villalobos, Alice E. (Frontiers in Veterinary Science, 2019)
People with disabilities and those working to train, provide and support assistance animals, along with their veterinary teams, would all benefit if they RETHINK their viewpoint and role when these very special relationships comes to an end. The end of the relationship may be when the assistance animal must retire, must be redirected or euthanized due to illness or cancer. The loss or separation at the end of an assistance animal’s service marks a heavy loss for the disabled person. Emotions emerge when the assistance animal is sick or has developed cancer or is approaching the difficult period known as “end of life.” Anticipatory grief and heartbreak may be very difficult to manage. We can help ease the burden of decision making when euthanasia is needed for the assistance animal. If the disabled person takes on the good shepherd role and if the veterinary team emulates the minister role at the end of life or at the end of the working relationship, heartache may be lifted from both sides of the leash.